2021
DOI: 10.1016/j.ekir.2020.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Circulating B Cells, Plasma Cells, and Treg Associate with ANCA Levels in ANCA-associated Vasculitis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Patients with AAV exhibit higher proportions of B lymphocytes and plasma cells than healthy controls. [ 16 , 17 ] Other studies have shown that rheumatologic diseases like AAV affect the risk of MM or other lymphoproliferative disorders progressed from monoclonal gammopathy of undetermined significance (MGUS). [ 18 ] In another cohort of 16 individual case studies, all patients were positive for anti-PR3 and anti-MPO antibodies and were diagnosed with MM.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AAV exhibit higher proportions of B lymphocytes and plasma cells than healthy controls. [ 16 , 17 ] Other studies have shown that rheumatologic diseases like AAV affect the risk of MM or other lymphoproliferative disorders progressed from monoclonal gammopathy of undetermined significance (MGUS). [ 18 ] In another cohort of 16 individual case studies, all patients were positive for anti-PR3 and anti-MPO antibodies and were diagnosed with MM.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results showed that there were antigen-speci c effector CD4 + T cells in peripheral blood during the acute infection stage of AAV, and the depletion of CD4 + T cells alleviated the progression of the disease [10]. As report, the B cells, plasma cells and Treg cells in circulating blood of AAV patients were higher than those in healthy controls [11]. Monocytes have also been shown to accumulate in crescents of necrotizing glomerulonephritis [12].…”
Section: Introductionmentioning
confidence: 85%